Assessment of Unilateral Spatial Neglect Using a Free Mobile Application for Italian Clinicians - Cipresso, Pietro; Pedroli, Elisa; Serino, Silvia; Semonella, Michelle; Tuena, Cosimo; Colombo, Desirée; Pallavicini, Federica; Riva, Giuseppe (Frontiers in Psychology, 2018)
Background: Unilateral Spatial Neglect (USN) is traditionally assessed with paper-and-pencil tests or computer-based tests. Thanks to the wide-spreading of mobile devices, and the extensive capabilities that they have in dealing complex elements, it is possible to provide clinicians with tools for cognitive assessment. Contemporary 3D engine is, in general generally, able to deploy complex 3D environments for iOS, Android and Windows mobile, i.e., most of the mobile phone and tablet operative systems. Results: This brand-new scenario and pressing requests from professionals, pushed us to build an application for the assessment of USN. Our first attempt was to replicate the classic cognitive tests, traditionally used at this purpose. Ecological assessment is difficult in real scenarios so we implemented virtual environments to assess patients’ abilities in realistic situations. At the moment, the application is available only for iPad and iPhone for free, from the Apple Store, under the name of “Neglect App.” The App contains traditional tests (e.g., barrage with and without distractors) and ecological tests (e.g., to distribute the tea in a table to close people). Scoring of each test is available to the clinicians through a database with the executed ecological tasks, that are stored locally. Conclusion: In conclusion, Neglect App is an advanced mobile platform for the assessment of Neglect.